A Definition of Rapid Weakening for Tropical Cyclones Over the Western North Pacific. Issue 20 (21st October 2019) - Ma, Zhanhong; Fei, Jianfang; Huang, Xiaogang
Abstract: The statistical characteristics of rapid weakening (RW) tropical cyclones over the western North Pacific are explored from 1988 to 2017. The RW is defined as approximately the 95th percentile of all 24‐hr over‐water weakening rates, corresponding to a 40 kt (20.6 m/s) or greater decrease in the maximum surface wind over a 24‐hr period. Statistical analysis suggests that RW tropical cyclones tend to possess higher intensities and faster translation than non‐RW tropical cyclones. Relative to the non‐RW cases, the RW cases occur in regions with a stronger meridional sea surface temperature (SST) gradient and smaller SST. The SST difference between RW and non‐RW cases is amplified during the weakening phase. Strong vertical wind shear plays a crucial role in leading to the RW events, while the contribution of midlevel dry‐air intrusion is found to be not statistically important in the western North Pacific basin. Key Points: A definition of RW for western North Pacific TCs is proposed, being 40 kt or more decrease in the maximum surface wind in 24 h. The RW cases tend to be stronger, move faster, and occur in regions with a sharper SST gradient compared with Non‐RW cases. Strong vertical wind shear plays a crucial role while midlevel humidity plays a minor role in contributing to RW events.